Adherence to guideline recommended medical therapies in type 2 diabetic patients with chronic critical limb ischemia. (December 2019) - Iacopi, Elisabetta; Coppelli, Alberto; Riitano, Nicola; Abbruzzese, Lorenza; Pieruzzi, Letizia; Goretti, Chiara; Piaggesi, Alberto
Abstract: Aim: The aim of this study was to evaluate the adherence to guideline recommended medical therapies in type 2 diabetic patients with chronic critical limb ischemia (CCLI). Methods: We retrospectively analyzed the data of 1315 admissions performed in our Department, focusing on diabetic foot patients (842–64%) of which 603 consecutive type 2 diabetic patients with CCLI (M/F(%): 73/27; age: 70.3 ± 10.4 yrs; diabetes duration: 17.3 ± 13.7 yrs; BMI: 27.7 ± 5.3 Kg/m 2 ; HbA1c 7.8 ± 1.8%) referred to a third-level Center from 2011 to 2015. We focused on medical therapy of diabetes, dyslipidemia, hypertension, peripheral vascular disease and smoke habits. Results: In total, at admission, 66.6% of patients had HbA1c levels higher than recommended; 65.9% of patients were on statins; 81.4% on anti-hypertensive treatment and 72.4% on antiplatelet drugs. Concerning smoke habits, 27% of patients were no-smokers; 41% former smokers and 32% active smokers. Among all patients, only 24% were prescribed all five guideline recommended therapies while 32% reached four out of five of these. As for patients treated with anti-hypertensive drugs, we observed higher levels of systolic pressure (138.0 ± 29.5 vs 107.7 ± 36.6 p < 0.02) while no differences were observed in diastolic pressure levels. Conclusions: In conclusion, when it comes to diabetic patients with a severe limb and life threatening clinical condition, we noticed a lower-than-expected application of international guideline-recommended medical therapies. In fact, only one out of four patients was following all the recommended therapies. Nevertheless, these patients did not reach the standard targets requested to prevent cardiovascular disease.